Os cocos: uma manifestação cultural em três momentos do século XX - Ayala, Maria Ignez Novais (Estudos Avançados, 1999)
THIS ARTICLE FOCUSES on a popular manifestation which grew in several parts of Paraíba State, mainly among blacks and their descendants. Oral literature, songs and dances are interwoven in that manifestation known as "coco". "Cocos" were first recorded, using scientific methods, in the 20's and 30's thanks to Mário de Andrade's initiative, which produced a large documentation. The wish to organize a precious heap of information on "cocos", based on direct observation and field recording with mechanical and electronic instruments, using techniques and methods which may allow judicious analyses of that Northeastern cultural manifestation, in an attempt to point out its characteristics, has been the motivation of our research going on in Paraíba since 1992. In this article the importance of the documentation amassed by Mário de Andrade and the members of the Missão de Pesquisas Folclóricas of São Paulo's Municipal Phonograph Record Collection is acknowledged; questions related to current poetry, song and dance manifestations are summed up, taking into account the dancers' and singers' life contextualization, the special meaning which the "coco" play has for them nearly becoming an identity affirmation. Furthermore, the popular cultural condition is analyzed within its social setting in which writing is hegemonic, making thus explicit the militant point of view adopted in this research.